OHMi Estarreja: an ecosystem highly anthropized where contamination is the unifying element towards interdisciplinarity - Bedell, Jean-Philippe; Guihard-Costa, Anne-Marie; Paiva, Cristiana; Machado, Diogo; Cachada, Anabela; Patinha, Carla; Durães, Nuno; Sousa, Ana Catarina; Beurier, Anne-Gaëlle; Ferreira da Silva, Eduardo (Comptes Rendus. Géoscience)
The Estarreja area (North of Portugal) has been subject to intense industrial pollution and host the second largest chemical industry complex in the country, which produced mainly ammonium sulphate, nitric acid and ammonium nitrate, but also synthetic resins. The CNRS’ Human–Environment International Observatory of Estarreja (OHMi Estarreja) aims to study the multiple effects of this industrial activity on the man-environment relationship, considering the temporal dimension, marked by changes in industrial practices. Another OHMi Estarreja originality is that human health projects are being carried out at the local level, under a double geochemical and socio-behavioral approach. Lastly, the Estarreja region is also part of one of the most important wetland ecosystems from Portugal, the Baixo Vouga Lagunar. This area is highly vulnerable and currently faces a set of natural and anthropogenic pressures. The overall interdisciplinary understanding of the risk induced by the chemical complex was possible by several complementary approaches: (a) spatial-temporal evolution of the contamination level, (b) health studies of the Estarreja population, and (c) societal changes in Estarreja area. The results showed a complex relationship between industrial pollution and health risks. During these first 10 years of OHMi existence, the bibliographic research as well as the study of the titles of the funded projects clearly show the interdisciplinarity in place to address this complex issue of human–environment interactions.